History of the United Netherlands, 1590b - Motley, John Lothrop, 1814-1877 (Salt Lake City, UT : Project Gutenberg, 2004)
"History of the United Netherlands, 1590b" by John Lothrop Motley is a historical account written during the mid-19th century. The book focuses on the complex and tumultuous events surrounding the struggle for independence in the Netherlands against Spanish domination, highlighting the larger conflicts in Europe during this period. The narrative serves to illustrate the broader themes of liberty and despotism through the lens of the Dutch fight for freedom. In this installment, Motley delves into the military campaigns and political intrigues of the late 16th century, particularly emphasizing the significant events leading up to the Twelve Years' Truce. The book recounts key battles, such as the Battle of Ivry, and the pivotal figures involved, including King Henry of Navarre and the Duke of Parma. Through detailed descriptions of warfare and diplomacy, Motley captures the fervent struggles for power and the deeply entrenched religious conflicts that characterized the era. The interplay of nationalism, ambition, and the tragic consequences of civil strife resonate throughout Motley's work, reflecting the enduring clash between the quest for self-governance and the oppressive forces of absolutism. (This is an automatically generated summary.)
Release date is 2004-01-01
This eBook was produced by David Widger
Keywords: Netherlands -- History -- Eighty Years' War, 1568-1648